(untitled) (Texas Journal of Engineering and Technology, 2023)
Numerous advancements in concrete technologies have significantly influenced structural systems. This review provides an overview of the existing body of research literature pertaining to hollow-core slabs. The existing body of literature pertaining to the current research can be classified based on prior investigations conducted on the topic of weight reduction of slabs. This paper incorporates the principal findings derived from prior research.